2011
DOI: 10.3168/jds.2010-3773
|View full text |Cite
|
Sign up to set email alerts
|

Somatotropic axis and concentrate supplementation in grazing dairy cows of genetically diverse origin

Abstract: Supplementing pasture-fed dairy cows with concentrates in early lactation was hypothesized to result in an earlier postpartum recoupling of the somatotropic axis in New Zealand (NZ)-type Holstein-Friesian dairy cows than in North American (NA)-type cows. To test this hypothesis, NA (n=30) and NZ (n=30) cows were allocated to 1 of 3 supplementation strategies (0, 3, or 6 kg of dry matter concentrate/d) for the first 12 wk of lactation in a completely randomized design and a 2×3 factorial arrangement. Production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
29
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 29 publications
13
29
1
2
Order By: Relevance
“…Liver IGF-1 synthesis is downregulated during early lactation despite increased growth hormone (GH) levels (Lucy et al, 2001). The greater plasma IGF-1 observed in SEMI is consistent with literature from grass-based systems showing an earlier recoupling of somatotropic axis when cows received 3 kg/day of concentrate, which was sufficient to decrease plasma GH, and increase IGF-1 and glucose concentrations (Grala et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Liver IGF-1 synthesis is downregulated during early lactation despite increased growth hormone (GH) levels (Lucy et al, 2001). The greater plasma IGF-1 observed in SEMI is consistent with literature from grass-based systems showing an earlier recoupling of somatotropic axis when cows received 3 kg/day of concentrate, which was sufficient to decrease plasma GH, and increase IGF-1 and glucose concentrations (Grala et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…These differences have been attributed to adaptations of somatotropic axis components that regulate nutrient partitioning ). Nonetheless, strain by system interactions for milk production, body reserve mobilization and accretion may not occur when cows are on a low plane of nutrition (Grala et al, 2011), which is the case in our experiment. In addition, it cannot be excluded that cow numbers may have been insufficient to allow the detection of eventual breed by system interactions.…”
mentioning
confidence: 73%
“…This study also showed that these differences in nutrient partitioning were underpinned by a far greater uncoupling of the somatotropic axis (Growth harmone IGF-1) in the North American strain compared with the New Zealand 70 strain with the New Zealand 90 intermediate. An increase in feed allowance had no effect on the milk production of the North American strain in early lactation, whereas it provoked an increased milk production in the New Zealand 70 strain (Grala et al, 2011).…”
Section: Introductionmentioning
confidence: 84%
“…Although an indirect measure of tissue status, these data provide further evidence that the adipose tissues of NA cows have lower rates of lipogenesis and hence more insulin-resistant compared with the NZ cows. Previous studies support the premise that the NA cows have a longer period of insulin insensitivity and uncoupling of the somatotrophic axis McCarthy et al 2009;Grala et al 2011). These phenomena result in an elevated growth hormone concentration, which in turn antagonizes insulin action, essentially blocking lipogenesis and promoting lipolysis and gluconeogenesis (Etherton et al 1987;Beswick & Kennelly, 1998).…”
Section: Discussionmentioning
confidence: 84%